1986
DOI: 10.1029/jb091ib08p08341
|View full text |Cite
|
Sign up to set email alerts
|

Geodesy by radio interferometry: Evidence for contemporary plate motion

Abstract: Analysis of 211 very long baseline interferometry observing sessions carried out between November 1979 and August 1984 has yielded estimates of the distances between various radio telescopes located inNorth America and Europe. The average rate of change of the distances between four radio telescopes in North America (Haystack Observatory, Massachusetts' Westford Radio Telescope, Massachusetts; George R. Agassiz Station, Texas' and Owens Valley Radio Observatory, California) and one in Europe (Onsala Space Obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(22 citation statements)
references
References 10 publications
0
22
0
Order By: Relevance
“…In addition to solid-Earth tides, displacement of land masses resulting from tidal shifts of water masses, called ocean loading, is measurable. The earliest evidence of contemporary motion of tectonic plates was found by Herring et al (1986), who reported that the increase in the baseline between Westford, MA, and Onsala, Sweden, based on data from 1980 to 1984, was 17˙2 mm/yr. A plot of the extensive measurements of the Westford-Onsala baseline is shown in Fig.…”
Section: Geodetic Measurementsmentioning
confidence: 99%
“…In addition to solid-Earth tides, displacement of land masses resulting from tidal shifts of water masses, called ocean loading, is measurable. The earliest evidence of contemporary motion of tectonic plates was found by Herring et al (1986), who reported that the increase in the baseline between Westford, MA, and Onsala, Sweden, based on data from 1980 to 1984, was 17˙2 mm/yr. A plot of the extensive measurements of the Westford-Onsala baseline is shown in Fig.…”
Section: Geodetic Measurementsmentioning
confidence: 99%
“…An important result of this effort has been the establishment of the International Celestial Reference Frame adopted by the IAU, which is based on 295 "defining" sources whose positions are known to an accuracy of about 40 as (Fey et al 2015). Another striking result of the geodetic VLBI work has been the detection of contemporary plate motions in the Earth's mantle, first measured as a change in the Westford-Onsala baseline at a rate of 17˙2 mm/yr (Herring et al 1986). The VLBI measurements of plate motions is shown in Fig.…”
Section: Very-long-baseline Interferometrymentioning
confidence: 99%
“…By 1992, several mobile sites have been occupied by GSI to control geodetic networks in Japan with unprecedented high accuracies (Tobita et al, 1993); these studies have detected plate motions (Matsuzaka et al, 1991). (Herring et al, 1986). Figure 2 shows the baseline length change in the Kashima-Kauai baseline for data obtained from 1984(Ryan et al, 1993 (Ryan et al, 1993).…”
Section: Summary Of Geodetic Vlbi Activities In Japanmentioning
confidence: 99%
“…Progress in Earth rotation studies (e.g., Tapley et al, 1985;Campbell et al, 1987) and determining a terrestrial reference frame (e.g., Boucher et al, 1993) in geodesy and detection of plate motion (e.g., Christodoulidis et al, 1985;Herring et al, 1986;Heki et al, 1987) in geodynamics are the most eminent examples.…”
Section: Introductionmentioning
confidence: 99%